The female presence in the photography of Lima magazines from the first decade of the 20th century - Torres Meza, Scarlett Estrella (2025)
The research work will analyze the presence of the female image in Peruvian photography of the twentieth century in its first decade, aiming to delve into their social position, the styles of representation, the elements that give unique characteristics, the beneficiaries with this innovation with images in private and public spaces presented in Lima magazines of the time. These photographs as clear outlines of the new era, relate their results to modernity and the creation of new technologies, and as a consequence of political, social and cultural changes that affect the image of women who, for the time, begin to appear in the public sphere more frequently, no longer only dependent on the image of a man, but allowing to show differentials in their identity from the photographic format, the clothing used and the elements that accompany it.